STRATEGI GURU DALAM MENGEMBANGKAN MODEL PEMBELAJARAN SOSIAL EMOSIONAL MELALUI PENERAPAN KURIKULUM MERDEKA ANAK USIA DINI DI TK AISYIYAH 1 - Suriati; Hasan, Ihlas; Ramadhan, Sahrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe teachers' strategies in developing a social emotional learning model through the implementation of the Merdeka Curriculum for early childhood at Aisyiyah Kindergarten 1. The approach used is descriptive qualitative with data collection techniques in the form of observation, interviews and documentation. The research results show that teachers at Kindergarten Aisyiyah 1 implement various child-centered learning strategies, such as daily habits, role-playing activities, and small group discussions that encourage children to recognize, manage, and express emotions positively. The Merdeka Curriculum provides flexibility for teachers in designing activities that suit children's social and emotional development needs. In conclusion, the implementation of the Independent Curriculum provides wider space for teachers to integrate social and emotional values ​​into learning contextually and meaningfully